Influence of Structural Defects on Excitonic Photoluminescence of Pentacene - Piryatinski, Yu.P.; Kurik, M.V. (Ukrainian Journal of Physics, 2022)
The exciton reflection, absorption, and photoluminescence spectra for single crystals and polycrystalline films have been studied in the temperature range of 4.2–296~K. A significant influence of structural defects arising during phase transitions on the exciton spectra of pentacene has been detected. The mechanisms of photoluminescence in single crystals and crystalline films of pentacene have been considered.